Adolescent pregnancy in Sao Tome and Principe: a cross-sectional hospital-based study - Alexandra Vasconcelos; Nelson Bandeira; Swasilanne Sousa; Filomena Pereira; Maria do Ceu Machado (BMC, 2022)
Abstract Background Pregnancy starts early in Sao Tome and Principe (STP) and rates of adolescent pregnancy increased 16% in recent years reaching a 27.3% prevalence. This study aimed to understand the pregnant adolescents' characteristics and factors associated to early childbearing in STP. Methods A cross-sectional hospital-based study was undertaken in Hospital Dr. Ayres de Menezes between 2016 and 2018 with a randomly selected total sample size of 518 mothers. Mothers' clinical records and interviews were used to collect relevant data. The results among adolescent girls 19 years of age and younger (n=104) were compared to adult mothers (n=414). A subgroup analysis of adolescent pregnant girls was also conducted. Statistically significance was considered at a p-value ≤0.05. Data were analysed using SPSS software. Results The study revealed that 20.1% were adolescent mothers. Pregnancy at a very early age (≤15) was experienced by 7.7%. The characteristics founded to be positively associated with adolescent pregnancy were: 1) being single (OR 0.39, 95% CI=0.2-0.6, p≤0.001); 2) having a relationship with the baby´s father for a period of less than one year (OR 0.16, 95% CI=0.09-0.3, p≤0.001); 3) lack of the baby´s father support (OR 0.41, 95% CI=0.2-0.7, p=0.002); 4) not using a contraceptive method (OR 0.33, 95% CI=0.2-0.5, p≤0.001), and 5) inappropriate knowledge concerning the identification of the newborn's danger signs (OR 15.7, 95% CI= 9-26, p≤0.001). Comparing pregnancy at very early age (≤15) to late (>18 and ≤19) adolescents, main differences were that previous contraceptives were not used at all in girls ≤15 years compared to 9.8% of late childbearing subgroup. Conclusions Unfavourable factors linked to adolescent pregnancies were absence of a contraceptive method, getting pregnant in the early first months of one relationship and to be single. Gap age difference between adolescents' partners, polygamous sexual relationships, previous abortion and having already other living children were also identified. Adolescents also had inappropriate knowledge of the identification of the newborns' danger signs. Before being sexually active, adolescents critically need sexual and reproductive health information provided by a healthy community and through school programmes on sexual education. Schools should promote girl's empowerment and awareness and, at the same time, reinforce boy's role in fatherhood and shared responsibilities. The government should work on the prevention of early sexual initiation, as well as on improving family planning programmes to protect them from pregnancy with special focus for the very early adolescent girls. None of these goals can be achieved if the government doesn't, simultaneously, improve educational and economic opportunities for girls.